Digital Marketing Analysis of Increasing Tourist Visits to Tourism MSMEs in Sorong Regency, Southwest Papua - Andi Sismar; Annisa Rosida Salsabila K; Almar Atus Sholeha; Futi Khaturrahmah; Dilla Astuti Ningsih; Imelda Desi Anggraini; Musriani; Hardiman F. Sanaba; Sabaria; Sudirman (IECON: International Economics and Business Conference, 2025)
The purpose of this study was to determine: the effect of digital marketing on increasing tourism visitors. This study uses a quantitative method. The population of this study were tourism MSME actors in the Sorong Regency area of Southwest Papua. The sampling technique was a saturated sample. So the total sample in this study was 150 people. Data analysis in this study was carried out using regression analysis method to evaluate the relationship between the variables studied. The action activities include: distributing questionnaires, collecting and analyzing data and conclusions. The results of this study reveal that digital marketing has a positive and significant effect on increasing the number of visitors to tourism MSMEs.